CREATIVE CITIES RESEARCH IN PENANG, MALAYSIA: A REVIEW OF CONCEPTUAL AND METHODOLOGICAL FRAMEWORK - Suet Leng, Khoo; Badarulzaman, Nurwati; Samat, Narimah; Sirat, Morshidi; Sheikh Dawood, Sharifah Rohayah (PLANNING MALAYSIA, 2015)
A heightened interest in the notions of ‘creative cities, creative industries and creative economy’ has propelled research in these emerging areas of the New Economy. As an emerging area, some conceptual and methodological issues need to be addressed prior to adopting the creative city paradigm as part of the strategic and policy framework towards a creative economy. This paper presents a review of key conceptual and methodological issues that need to be considered when conducting research on creative cities in Malaysia. The conceptual and methodological issues relating to creative cities and creative industries should be addressed and dealt with in order to facilitate an enabling framework for contemporary research in this emerging area.